2018
DOI: 10.3847/1538-4357/aaeb31
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Exoplanet Masses and Radii: A Nonparametric Approach

Abstract: A fundamental endeavor in exoplanetary research is to characterize the bulk compositions of planets via measurements of their masses and radii. With future sample sizes of hundreds of planets to come from TESS and PLATO, we develop a statistical method that can flexibly yet robustly characterize these compositions empirically, via the exoplanet M–R relation. Although the M–R relation has been explored in many prior works, they mostly use a power-law model, with assumptions that are not flexible enough to captu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(113 citation statements)
references
References 49 publications
3
108
2
Order By: Relevance
“…This low value for the low mass break is below most planets in the sample, perhaps indicating weak support for including this break based on the CKS sample. This is supported by the nonparametric mass-radius relation fit by Ning et al (2018), which found no evidence for a low mass break in the mass-radius relation with the current mass-radius sample. The scatter parameters σ 0 , σ 1 , σ 2 that we retrieve are higher across the board (0.07 +0.02 −0.01 vs 0.04 +0.01 −0.01 , 0.27 +0.03 −0.03 vs 0.15 +0.02 −0.01 , and 0.11 +0.03 −0.02 vs 0.07 +0.01 −0.01 , respectively).…”
Section: Model Fitssupporting
confidence: 59%
“…This low value for the low mass break is below most planets in the sample, perhaps indicating weak support for including this break based on the CKS sample. This is supported by the nonparametric mass-radius relation fit by Ning et al (2018), which found no evidence for a low mass break in the mass-radius relation with the current mass-radius sample. The scatter parameters σ 0 , σ 1 , σ 2 that we retrieve are higher across the board (0.07 +0.02 −0.01 vs 0.04 +0.01 −0.01 , 0.27 +0.03 −0.03 vs 0.15 +0.02 −0.01 , and 0.11 +0.03 −0.02 vs 0.07 +0.01 −0.01 , respectively).…”
Section: Model Fitssupporting
confidence: 59%
“…Assuming that the V1298 Tau planets will follow the mature exoplanet mass-radius relation of Chen & Kipping (2017) in the future, we calculated the expected final radii to estimate that the planets might contract by 40-90% (68% confidence interval) over the subsequent evolution of the system. These results are not changed significantly when adopting the nonparametric mass-radius relation of Ning et al (2018).…”
Section: Estimating Planet Massesmentioning
confidence: 85%
“…The planet transit time was uniform over the timespan of the observations, and inclination was uniform from 0 − 90 • . The planet mass was log-normally distributed, M p ∼ 10 2.5±0.5 M ⊕ , based on the expectation for Jupiter-radius objects from Ning et al (2018). For the moon model, we allowed the transit time to vary uniformly over the entire visit.…”
Section: Astrophysics Modelmentioning
confidence: 99%